Co-crystallization and polymorphic behaviour of 5-fluorouracil. Issue 13 (30th November 2018) - Enkelmann, Dennis D.; Handelmann, Jens; Schauerte, Carsten; Merz, Klaus
Abstract : Hydrogen donors and acceptors in 5-fluorouracil allow the formation of co-crystalline compounds with nontoxic co-formers of the GRAS list and an alternative target-oriented synthon approach from methanol or ethanol to form II of 5-fluorouracil is presented. Abstract : Syntheses and single-crystal characterization of two co-crystalline 5-fluorouracil compounds with nontoxic co-formers of the GRAS list, succinic acid and adipic acid, are presented. Furthermore, the target-oriented synthon approach from methanol or ethanol (technical grade) to polymorphic form II, which is hitherto only accessible from dry nitromethane, is described.